Itching sensation and neuronal sensitivity of the skin. Issue 1 (6th August 2015) - Ham, H.; An, S. M.; Lee, E. J.; Lee, E.; Kim, H. O.; Koh, J. S.
Abstract : Background: Sensitive skin is a universal term in the field of cosmetology. In addition, the development and demand for sensitive skin cosmetics is increasing. However, there is no appropriate method for detecting sensitive skin. Methods: We analyzed the relationship between the frequency of response at each sensation (stinging, burning, and itching) during a lactic acid sting test and the current perception threshold (CPT) value of each frequency. To reconfirm this relationship, we analyzed differences of the CPT value (5 Hz) between the itch responder and non‐itch responder groups. Results: There is a significant correlation between itch sensation and CPT values of 5 Hz. The itch responder group showed significantly lower sensory perception value of 5 Hz than the non‐itch responder group. Conclusion: The CPT value (5 Hz) can be used for scanning for itching sensations when a cosmetic or its ingredients possibly cause the sensation.